25-hydroxyvitamin D and testosterone levels association through body mass index: A cross-sectional study of young men with obesity - Damas-Fuentes, Miguel; Boughanem, Hatim; Molina-Vega, María; Tinahones, Francisco J.; Fernández-García, José C.; Macías-González, Manuel (Frontiers in Endocrinology, 2022)
Backgrounds. Vitamin D and testosterone deficiency have been widely related to obesity. However, only a few studies have investigated the effect of vitamin D on testosterone in the context of obesity, in which controversial results have been raised. Objectives. The purpose of this study was to determine the relationship between serum 25-hydroxyvitamin D (25(OH)D) and testosterone levels in young men with different grade of obesity. Design and methods. This cross-sectional study included 269 healthy young men with obesity (body mass index (BMI) ≥ 30 kg/m2). Participants were divided into two groups based on their serum 25(OH)D levels (134 subjects with vitamin D sufficiency and 135 participants with vitamin D deficiency, according to the 50th percentile of 25(OH)D). Serum 25(OH)D and sex hormones have been measured. The relationships between 25(OH)D, sex hormones, and obesity grades were investigated with linear and binary logistic regression analyses, as well as mediation analysis. Results. Compared to the 25(OH)D sufficiency group, total and free testosterone levels were found to be decreased, whereas serum androstenedione levels were increased in the 25(OH)D deficiency group (p<0.05). Using multivariable lineal regression analyses, 25(OH)D was correlated with the majority of sex hormones (p<0.05). When mediation with BMI was performed, the direct effect between 25(OH)D and sex hormones disappeared, and only the indirect effect via BMI remained (demonstrating the importance of BMI). Furthermore, after controlling for age and smoking status, we discovered that total testosterone and SHBG were both significantly associated with 25(OH)D (p<0.05) in subjects with obesity type III. Using a mediation analysis, we discovered that BMI had a partial effect on the association between 25(OH)D and total testosterone levels in morbidly obese participants, indicating that a direct association between 25(OH)D and total testosterone levels, and that BMI partially mediated this association. Conclusions. Serum 25(OH)D is associated with total testosterone levels in only those subjects with morbid obesity, suggesting a specific benefit in severe cases of obesity. Additional research is needed to elucidate possible common mechanisms.